Financial crisis and stock market linkages - Gabriel, Vítor (2016)
This paper investigates interdependencies and linkages between international stock markets in the shortrun. Thus, twelve European and non-European markets were selected, and the period from 4 October 1999 to 30 June 2011 was chosen, which includes the Dot-Com crisis and the recent Global Financial Crisis. To investigate interdependence and dynamic linkages between stock markets, a vector autoregressive model, the concept of Granger causality and impulse-response functions were considered. We concluded that the global financial crisis contributes to the intensification of the interdependence between stock markets.